PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN BUDIDAYA LEBAH TRIGONA DI DESA MENGGARE SLAHUNG PONOROGO - Siti Zazak Soraya; Ferika Andani; Tasaki Fattah Hidayat Afriansyah; Dani Rizki Fadilah (LPPM Universitas Islam Darul 'Ulum Lamongan, 2024)
Menggare Village in Slahung Ponorogo has considerable potential to develop trigona beekeeping because many plants, including acacia trees, a food source for these bees, still surround it. Therefore, the people in Menggare Village have promising opportunities in the Arizona beekeeping business. This trigona beekeeping training activity aimed to provide an understanding of trigona bees and their benefits and guidelines for cultivating trigona bees as a first step to doing business in this field. This training was held on Sunday, 23 July 2023, at the Menggare Village Hall, Slahung, Ponorogo, with 13 participants. The approach used in this activity is an asset-based community development (ABCD) approach, focusing on exploiting the potential that already exists in the community. The results of this training showed that some people are very enthusiastic about developing trigonal beekeeping. This success can be attributed to the high selling value and the ease of cultivating trigona bees. In addition, this dedication also positively impacts improving the quality of human resources and the local economy.